2018
DOI: 10.1111/voxs.12411
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and causes of deferral amongst voluntary non‐remunerated blood donors from Pakistan – a single‐centre study

Abstract: Background Amidst a system dependent on replacement donors in Pakistan, The Indus Hospital Blood Centre predominantly recruits voluntary non‐remunerated blood donors (VNRBD) to ensure provision of safe blood. Furthermore, due to unsafe practices of reuse of syringes in Pakistan, an additional criterion was added, deferring donors on recent history of therapeutic injections for medicinal purposes. Methods During the study period of 37 months (Dec 2013–Dec 2016), all potential donors visiting blood drives and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…Rabeya et al showed 40.7% cases of deferrals due to low hemoglobin being predominantly females, but in our study, only 1.4% of the deferred cases were females [16]. In contrast to our results, a single-center study conducted in one of the blood centers in Pakistan showed therapeutic injections as the significant reason for blood donor deferrals, with low hemoglobin being second in the list [18]. An interesting study was conducted in South Pakistan to assess the deferral pattern on the basis of the peripheral count.…”
Section: Discussioncontrasting
confidence: 99%
“…Rabeya et al showed 40.7% cases of deferrals due to low hemoglobin being predominantly females, but in our study, only 1.4% of the deferred cases were females [16]. In contrast to our results, a single-center study conducted in one of the blood centers in Pakistan showed therapeutic injections as the significant reason for blood donor deferrals, with low hemoglobin being second in the list [18]. An interesting study was conducted in South Pakistan to assess the deferral pattern on the basis of the peripheral count.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar results were reported previously where the high deferral rate was due to increased use of therapeutic agents amongst the population. 29 Drugs differ widely by structure and properties and include analgesics and antibiotics that result in a few days deferral to some growth hormones that result in permanent deferral. The use of drugs is widespread amongst prospective blood donors and is expected to rise due to many of them being on long-term treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Donation was deferred in the current study due to recent medication ingestion, which was a major contributing factor. Due to a rise in the usage of therapeutic drugs in the general population, similar outcomes have been seen [56]. Structure and qualities of drugs vary greatly, ranging from analgesics and antibiotics that only have a short-term effect to growth hormones that have a long-term effect.…”
Section: Discussionmentioning
confidence: 94%